The Sense of National Belonging and Identity in Selected Works of Nikos Kazantzakis, Kamala Markandya, and Ahlam Mosteghanemi (Journal of the College of Basic Education, 2022)
The feeling that a new start ought to be made in politics, society, or literature, is always associated with worldwide wars, national catastrophes, or any other mishaps which were haunted by deep-rooted memories of fear, anger, or sickness. The results or consequences could begin to transform their experience into social, political, and literary aspects of everyday life interactions. What is of great concern in the present study lies in tracing the line of development of the national sense of belonging in the works of three conspicuous writers: Kazantzakis, Markandaya, and Mosteghanemi. Chronologically, their works extended over a long period of time that starts from the 1920s up to the present time. Each writer was driven by a different motive or point of view to visualize her/his national sense of belonging.